BENZODIAZEPINE USE AMONG RESIDENT DOCTORS IN TERTIARY CARE HOSPITAL - Khan, Aftab Alam; Din, Imtiaz ud; Khan, Adil Naseer; Hanif, Humera; Ullah, Imran; Nawaz, Haq (Journal of Ayub Medical College Abbottabad, 2019)
Background: Benzodiazepines (BZD) are some of the most common medications in the world. Benzodiazepines useful in treating anxiety, insomnia, agitation, seizures, muscle spasms, alcohol withdrawal. Benzodiazepines are generally considered safe and well tolerated but are commonly misused and taken in combination with other drugs of abuse. The usage and prescription of BDZ in most developed countries are tightly regulated. This is however, not true in developing countries where these medicines are available over-the-counter (OTC). This study was carried out to assess the benzodiazepine use in Ayub Teaching Hospital Trainee doctors. Methods: This was a cross sectional study carried out in Ayub Teaching Hospital between January and December 2018. Sample size was calculated to be 276 using WHO sample size calculator. These 276 residents and house officers were selected using stratified random sampling to ensure the representation from every year of residency. Results: Hundred and nine (48.7%) participants responded positively to the use of BZD. Male doctors were more likely 57 (52.3%) to use BZD as compared to their female colleges. Most of the doctors 71 (65.1%) purchased BZD over the counter without prescription. Alprazolam was the most preferred benzodiazepine by doctors regardless of their specialty and year of residency except in specialty of Anaesthesia in which prevalence of Midazolam was the highest. This preference of Alprazolam by doctors of all specialty was statistically significant (p=0.007). Conclusion: Because of the knowledge about medicines and tendency to self-treat, doctors are prone to BZD abuse. Doctors working in psychiatry are more likely to use BZD with Alprazolam the BZD of choice. Keywords: Benzodiazepines; Alprazolam; Drug Abuse; Resident Doctors